2022
DOI: 10.1371/journal.pone.0278708
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a proteomic profile associated with organ dysfunction and mortality of sepsis and septic shock

Abstract: Introduction The search for new biomarkers that allow an early diagnosis in sepsis and predict its evolution has become a necessity in medicine. The objective of this study is to identify, through omics techniques, potential protein biomarkers that are expressed in patients with sepsis and their relationship with organ dysfunction and mortality. Methods Prospective, observational and single-center study that included adult patients (≥ 18 years) who were admitted to a tertiary hospital and who met the criteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 64 publications
0
5
0
Order By: Relevance
“…In a study by Adolfo et al, an analysis of plasma proteins in sepsis patients and their correlation with organ dysfunction and mortality revealed that the decrease in APOH had a strong association with lower mortality. This suggested that APOH acts as a lipoprotein with a protective effect on mortality [ 16 ]. Similarly, El-Assaad et al observed a decrease in APOH levels in male sepsis patients compared to healthy male controls.…”
Section: Discussionmentioning
confidence: 99%
“…In a study by Adolfo et al, an analysis of plasma proteins in sepsis patients and their correlation with organ dysfunction and mortality revealed that the decrease in APOH had a strong association with lower mortality. This suggested that APOH acts as a lipoprotein with a protective effect on mortality [ 16 ]. Similarly, El-Assaad et al observed a decrease in APOH levels in male sepsis patients compared to healthy male controls.…”
Section: Discussionmentioning
confidence: 99%
“…The participation of OS in septic shock and MOF has been previously reported [46,47]. The adaptation of the organism in the initial phases of OS, to balance the overproduction of reactive species (ROS) through processes of genetic overexpression and enzymatic activation, is crucial when the antioxidant systems are overcome.…”
Section: Discussionmentioning
confidence: 99%
“…32,33 A proteomic study of 141 patients with sepsis indicated that serpinf1 was highly associated with organ dysfunction and Serpinc1 was highly associated with mortality. 34 Vtn was a key regulator of coagulation, serum VTN level was associated with sepsis-associated acute liver injury and pediatric intensive care unit (PICU) mortality, and VTN plus PRISM III was a powerful predictor of PICU mortality in pediatric patients with sepsis. 35 Fgb played a key role in coagulation and inflammation, which also associated with mortality and organ dysfunction of patients with sepsis.…”
Section: Discussionmentioning
confidence: 99%
“…The top 10 proteins within PPI network most associated with disease biology might be key drivers of UMI-77 in treatment of sepsis . Apoa2 and Apoa4 were important apoproteins, mainly involved in the synthesis of high-density lipoprotein, which could protect blood vessels and prevent atherosclerotic diseases such as cerebral thrombosis and coronary heart disease. , A proteomic study of 141 patients with sepsis indicated that serpinf1 was highly associated with organ dysfunction and Serpinc1 was highly associated with mortality . Vtn was a key regulator of coagulation, serum VTN level was associated with sepsis-associated acute liver injury and pediatric intensive care unit (PICU) mortality, and VTN plus PRISM III was a powerful predictor of PICU mortality in pediatric patients with sepsis .…”
Section: Discussionmentioning
confidence: 99%